Jupiter's North Equatorial Belt expansion and thermal wave activity ahead of Juno's arrival - Fletcher, L; Orton, G; Sinclair, J; Donnelly, P; Melin, H; Rogers, J; Greathouse, T; Kasaba, Y; Fujiyoshi, T; Sato, T; Fernandes, J; Irwin, P; et al. (Wiley, 2017)
The dark colors of Jupiter's North Equatorial Belt (NEB, 7–17°N) appeared to expand northward into the neighboring zone in 2015, consistent with a 3–5 year cycle. Inversions of thermal-IR imaging from the Very Large Telescope revealed a moderate warming and reduction of aerosol opacity at the cloud tops at 17–20°N, suggesting subsidence and drying in the expanded sector. Two new thermal waves were identified during this period: (i) an upper tropospheric thermal wave (wave number 16–17, amplitude 2.5 K at 170 mbar) in the mid-NEB that was anticorrelated with haze reflectivity; and (ii) a stratospheric wave (wave number 13–14, amplitude 7.3 K at 5 mbar) at 20–30°N. Both were quasi-stationary, confined to regions of eastward zonal flow, and are morphologically similar to waves observed during previous expansion events.